2010
DOI: 10.2190/ag.71.2.d
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Reminiscence Functions Scale for the Portuguese Population: A Preliminary Report

Abstract: The aim of the present study was to assess the psychometric properties of a version in Portuguese of the Reminiscence Functions Scale. Total sample was composed of 628 participants aged between 18 and 92 years, divided into three groups according to their age (18-24 years, n = 249; 26-54 years, n = 174; 55 and older, n = 205). Results indicated a five-factor solution for the Portuguese version of the Reminiscence Functions Scale, which accounted for 54% of the variance with good internal consistency (mean alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…To do so, we used empirical data from a new sample of Jordanian participants while testing its measurement invariance across gender. Cronbach's α values (internal consistency) for the six factors of the adjusted AARFS are marginally higher than those reported for the original RFS (Webster, 1993, 1997) and other versions of the RFS such as the Spanish (Ros et al, 2016), Canadian (Robitaille et al, 2010), Chinese (Lou & Choy, 2014), and Portuguese (Gonçalves et al, 2010) versions. This indicates good internal consistency for the six‐factor ARFS.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…To do so, we used empirical data from a new sample of Jordanian participants while testing its measurement invariance across gender. Cronbach's α values (internal consistency) for the six factors of the adjusted AARFS are marginally higher than those reported for the original RFS (Webster, 1993, 1997) and other versions of the RFS such as the Spanish (Ros et al, 2016), Canadian (Robitaille et al, 2010), Chinese (Lou & Choy, 2014), and Portuguese (Gonçalves et al, 2010) versions. This indicates good internal consistency for the six‐factor ARFS.…”
Section: Discussionmentioning
confidence: 66%
“…Although former quantitative studies support the seven and eight‐factor models of the RFS (Webster, 1993, 1997), no known studies on the factorial validity of this scale have been conducted among Arabic speakers. Variations of the RFS factor model have been supported through EFA and CFA, starting with the original seven and eight‐factor English versions (Webster, 1993, 1997), and including a seven‐factor modified version (Shellman & Zhang, 2014), a five‐factor Portuguese version (Gonçalves et al, 2010), and a four‐factor Chinese version (Lou & Choy, 2014). Mixed results from factor analyses of the original RFS and other translated versions of the RFS (Lou & Choy, 2014; Robitaille et al, 2010; Ros et al, 2016) have demonstrated the need to continue testing the psychometric properties of the RFS to confirm its validity among diverse populations and cultural contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations